2014
DOI: 10.1007/s00606-014-1152-3
|View full text |Cite
|
Sign up to set email alerts
|

Nectaries and male-biased nectar production in protandrous flowers of a perennial umbellifer Angelica sylvestris L. (Apiaceae)

Abstract: Nectar is the most common floral pollinator reward. In dichogamous species, floral nectar production rates can differ between sexual phases. We studied the structure of nectaries located on the stylopodium and nectar production in protandrous umbellifer Angelica sylvestris. Our study species produced nectar in both floral sexual phases. Nectar sugar concentration was low (on average 22 ± 11 %, mean ± SD) and the nectar hexose rich and composed of sucrose, glucose, fructose and a small amount of amino acids, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 66 publications
(90 reference statements)
2
20
0
3
Order By: Relevance
“…This would be difficult for pollinators to access. Such presentation of nectar may act as a phenotypic filter, preventing insects other than flies, with have a cushion-like labium, to gather floral rewards (Stpiczyńska et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…This would be difficult for pollinators to access. Such presentation of nectar may act as a phenotypic filter, preventing insects other than flies, with have a cushion-like labium, to gather floral rewards (Stpiczyńska et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Its dichogamous flowers are arranged into large inflorescences-compound umbels of different orders. Like many other umbellifers (Stpiczyńska et al 2015), within individual flower fennel demonstrates functional protandry. At first, flowers pass through a male functional stage with active anthers and then through the female functional stage with active stigma.…”
Section: Study Speciesmentioning
confidence: 98%
“…It has been previously found that in dichogamous species nectar production if often different between sexual stages. For example, in Angelica sylvestris it was three times lower during the stigma receptive period (Stpiczyńska et al 2015). Therefore, it is more likely that due to functional protandry and different floral nectar production between sexual phases, not all insects visit both types of flowering umbels.…”
Section: Insect Dynamicsmentioning
confidence: 99%
“…Some taxa have been investigated for secretion biology, e.g. Angelica sylvestris, for which the floral nectar production rates can differ between sexual phases (Stpiczyńska, Nepi, & Zych, 2015). Therefore, the lack of studies on the melliferous potential of other species in the Apiaceae is probably linked with their uniformity in their floral appearance, and their 'weak' melliferous potential probably hides a very large variability (10 to 500 kg/ha).…”
Section: Melliferous Potential Vs Botanical Featuresmentioning
confidence: 99%